Preparation and Characterization of Magnetic NiFe2O4 Decorated Exfoliated Graphite via Sol-Gel Method - Trung Sy, Do; T. Nguyen, Hong-Tham; Thanh Nguyen, Trung; Van Thinh, Pham (Asian Journal of Chemistry, 2020)
In present study, a composite material was synthesized from expanded graphite (EG) and nickel ferrite (NiFe2O4) via the sol-gel method. The composite was then structurally and morphologically characterized which confirmed that NiFe2O4 is successfully incorporated in the expanded graphite matrix after impregnation. For component characterization, energy diffraction scattering was used. X-ray diffraction (XRD) was employed to determine the physical structure of the nanocomposites. Lastly, pore size structure of EG@NiFe2O was examined via the nitrogen adsorption/desorption isotherm and pore size distribution plot.